A rhesus macaque intragastric challenge model for evaluating the safety, immunogenicity, and efficacy of live-attenuated Shigella dysenteriae 1 vaccine candidates - Ruamsap, Nattaya; Imerbsin, Rawiwan; Khanijou, Patchariya; Gonwong, Siriphan; Oransathit, Wilawan; Barnoy, Shoshana; Venkatesan, Malabi M.; Chaudhury, Sidhartha; Islam, Dilara (Frontiers in Microbiology, 2024)
Shigellosis continues to carry a significant burden of disease worldwide, particularly in Asia and Africa where it remains a major cause of illness and death among children. Due in part to the lack of suitable animal models for pre-clinical evaluation, a licensed Shigella vaccine has still not been developed. In this study, we demonstrate using an intragastric adult rhesus macaque challenge model to evaluate the safety, immunogenicity, and efficacy of five live-attenuated Shigella dysenteriae 1 vaccine candidates based on the 1617 parent strain. S. dysenteriae 1 vaccine strains include WRSd1, a previously tested vaccine candidate with deletions to virG(icsA), stxAB and fnr, along with WRSd2, WRSd3, WRSd4, and WRSd5 that also had the virG and stxAB deletions but contained fnr. WRSd3 and WRSd5 had additional deletions to Shigella enterotoxin gene senA and its paralog senB and WRSd5 had an additional deletion of msbB2. Rhesus monkeys were immunized three times (2 days apart) with a target dose of 2x10^10 CFU of the vaccine strains and 30 days after the last immunization, all monkeys were challenged with a target dose of 2x10^9 CFU of S. dysenteriae 1 1617 wild-type strain. Safety, immunogenicity, and efficacy was evaluated by monitoring physical signs and symptoms as well as immunologic and inflammatory markers following immunization and challenge. Three vaccine strains (WRSd1, WRSd3, and WRSd5) showed adverse effects of vomiting and loose stool following the first dose, but all five strains were well tolerated in the second and third dose. All vaccine strains induced significant IgA and IgG antibody responses and antibody-secreting cells. Following challenge, no vaccinated animal showed shigellosis symptoms of vomiting or loose/water stool, compared to 39% and 61%, respectively, for control monkeys. Using an aggregate clinical score to assess Shigella attack rates following challenge, control animals had a 72% attack rate compared to a 13% attack rate for vaccinated animals, corresponding to a relative risk reduction of 81%. We discuss the strengths and limitations of using this NHP model for evaluating safety, immunogenicity, and efficacy of live-attenuated Shigella vaccine candidates prior to conducting Phase 1 or more advanced-stage clinical trials.